2011
DOI: 10.1111/j.1463-1326.2011.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a long-acting GLP-1 mimetic (PF-04603629) on pulse rate and diastolic blood pressure in patients with type 2 diabetes mellitus

Abstract: PF-04603629, an exendin-transferrin fusion protein, is a long-acting glucagon-like peptide-1 (GLP-1) mimetic. This randomized, double-blind study characterized the safety and pharmacodynamics of a single dose of PF-04603629 (n = 57; 1-70 mg) or placebo (n = 14) in subjects with type 2 diabetes mellitus (T2DM). There were dose-dependent decreases from baseline in day 6 glucose area under the curve following a mixed meal test (-27 ± 12% with 70 mg). Most treatment-related adverse events were gastrointestinal, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Effectively, this is thought to be the mechanism that enables GLP‐1 RAs to lower energy intake, thereby reducing body weight, although to a varying degree. The increase in pulse rate reported with semaglutide treatment has also been previously reported in, for example, liraglutide‐ and exenatide‐treated participants, although the potential mechanisms behind this haemodynamic effect are unclear …”
Section: Discussionmentioning
confidence: 54%
“…Effectively, this is thought to be the mechanism that enables GLP‐1 RAs to lower energy intake, thereby reducing body weight, although to a varying degree. The increase in pulse rate reported with semaglutide treatment has also been previously reported in, for example, liraglutide‐ and exenatide‐treated participants, although the potential mechanisms behind this haemodynamic effect are unclear …”
Section: Discussionmentioning
confidence: 54%
“…20 A more recently published study of the longacting GLP-1 agent PF-04603629 reported a substantial rise in the heart rate (a mean increase of 23 bpm at 24 h after injection of the higher dose studied), together with a rise in the diastolic blood pressure. 21 While there is no evidence to date that these agents (short-acting or long-acting) increase cardiovascular event rates, safety data are limited by short follow-up duration. 22 A longer term follow-up is underway but will take a number of years to complete.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In humans (2,7,9,10,24,26,27,38,43), GLP-1 has a modest acute impact on hemodynamics. In most reports (2,26,27,38,43), the studies have not been designed to elucidate primarily hemodynamic effects of GLP-1; however, even when hemodynamics were measured continuously, the results were ambiguous.…”
mentioning
confidence: 99%